Rancangan Alat Pelepas Pin Piston pada Motor Piston Continental IO-470 dan Lycoming O-360 dengan Menggunakan Pompa Hidrolik di Prodi Teknik Pesawat Udara STPI - Ichsan Haryanto, Erlana; Rabati, Saddam; Al Asyari, Muawal (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2020)
Supporting factors for the achievement of these objectives in the piston engine workshop, which provides experience in maintenance of piston engines such as the Teledyne Continental IO-470 and Avco Lycoming O-360. A wide variety of tools currently available, both in terms of use and function, but not all components can be installed and removed using tools, without special tools. In aircraft specific maintenance, that is to repair and repair components for safe repairs, for example a 2000-hour inspection where checks such as engines, propellers, landing gear etc. One of them is when checking the engine which is done by removing the piston pin in accordance with the procedures in the maintenance manual, in the process of implementing it in the engine workshop the piston still uses a hammer and wood for release, with the force released from the hammer slip, as for some internal factors of the human itself such as stress and fatigue. From the observations of the force produced by the hammer with an average distance of the object at 0.3 m, the time required is 0.11 seconds, then the pin changes 0.009 m, the new force issued when hammering 4.95N and the force required 14.3 times to open piston pin, While to release the piston pin with six cylinders issued a total of 425.31N. Therefore, to improve safety in treatment, the authors used a piston pin release tool using a hydraulic pump, with a total design force of 425.31N issued on the actuator, using the Pascal principle so that the force for manual hand crank was 42.17N. And this tool can also use an AC motor to pump fluid with 500watt power and 2500rpm rotation